(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The Goods and Services Tax (GST), implemented in India on July 1, 2017, has been regarded as the most significant milestone in the history of taxation since Independence. The GST was planned to be implemented in April 2010, but was postponed due to political issues and conflict of interests of the stakeholders. The main purpose of the GST is to simplify the taxation system by subsuming all sorts of indirect taxes like, Central Excise, VAT, Sales Tax, and Service tax and implement ‘one nation one tax’ system in India. The objective of the paper is to examine the working of the GST and its prospects in India. As GST has been recently implemented only recently, the full impact of the system is still awaited. The research is exploratory in nature, and uses secondary sources of data, including journals, newspapers, websites of various relevant authorities, etc. The conclusion being positive in tone suggest several ways through which the GST can be reformed.